2017
DOI: 10.1016/j.jpain.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

OPRM1 Methylation Contributes to Opioid Tolerance in Cancer Patients

Abstract: Cancer patients in pain require high doses of opioids and quickly become opioid-tolerant. Previous studies have shown that chronic cancer pain as well as high-dose opioid use lead to mu-opioid receptor downregulation. In this study we explore downregulation of the mu-opioid receptor gene (OPRM1), as a mechanism for opioid tolerance in the setting of opioid use for cancer pain. We demonstrate in a cohort of 84 cancer patients that high-dose opioid use correlates with OPRM1 hypermethylation in peripheral leukocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 38 publications
1
16
1
Order By: Relevance
“…In that study, a methylating effect of opioid treatment had been proposed based on higher methylation levels in opioid treated than in non-opioid treated pain patients. This effect has been reproduced independently [71]. Nevertheless, the global methylation levels of in median 80% in that study [23] agreed with the presently observed levels.…”
Section: Discussionsupporting
confidence: 80%
“…In that study, a methylating effect of opioid treatment had been proposed based on higher methylation levels in opioid treated than in non-opioid treated pain patients. This effect has been reproduced independently [71]. Nevertheless, the global methylation levels of in median 80% in that study [23] agreed with the presently observed levels.…”
Section: Discussionsupporting
confidence: 80%
“…This may in turn lead to increased need for medication to treat the symptoms of opioid withdrawal. The associations between hypermethylation of the OPRM1 promoter after chronic opioid exposure, decreased OPRM1 gene expression, reduced pain tolerance and subsequent need for opioid medications have been showed in an adult cancer population, as well as in postoperative adult patients …”
Section: Discussionmentioning
confidence: 99%
“…Inadequate pain management in cancer patients has been linked to hypermethylation of OPRM1 , yielding a decreased response to the analgesic effects of opioids. Chronic or high-dose use of opioids was correlated with this hypermethylation and downregulation of receptors, confirming a mechanism of tolerance 69. Furthermore, the presence of a specific A118G polymorphism in OPRM1 leads to a less active receptor that has been linked to individuals with reduced analgesic responses to morphine postoperatively 70…”
Section: Biological Polymorphisms Involved In Painmentioning
confidence: 84%